Need, merit or self-interest – what determines the allocation of aid? - Hoeffler, A; Outram, V (CSAE (University of Oxford), 2008)
Previous studies into aid allocation have concluded that foreign aid is allocated not only according to development needs but also according to donor self-interest. We revisit this topic and allow for donor as well as recipient specific effects in our analysis. Our results indicate that roughly half of the predicted value of aid is determined by donor specific effects. Of the remaining variation, recipient need accounts for 36 percent and donor self-interest for about 16 percent. This suggests that the previous literature has overstated the importance of donor self-interest. However, bilateral donors seem to place little importance on recipient merit. Recipient merit, measured by growth, democracy and human rights, accounts for only two percent of predicted aid.